DRIVERS OF CUSTOMER LOYALTY TOWARDS BANKING SERVICES. THE CASE OF ISLAMIC BANK IN INDONESIA - Novia Putri, Riesdha; Haizam Mohd Saudi, Mohd; Faizun Mohamad Yazid, Mohd (International Journal of Psychosocial Rehabilitation, 2020)
The purpose of this study is to evaluate the relationships between the factors that drive customer loyalty towards Islamic Banking in Indonesia. The study tested six predictors that were recommended by previous research and literature review. Those factors are competitiveness, efficiency, services, competency of managers, accessibility and ranges of services. This research used quantitative method thus data were collected using the questionnaire. 275 questionnaires were distributed at selected banking outlets in 5 major cities and out of that, only 252 are usable. The balance 23 were rejected mainly because not meeting the selection criteria and incomplete data. Results indicates that all factors were significantly influence towards customer loyalty except accessibility and services. Markets’ players should take note on the findings as it is important for their future marketing plan in capturing more customers and strengthen their business strategy towards business growth and sustainability.